Deep material networks for efficient scale-bridging in thermomechanical simulations of solids - Gajek, Sebastian (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2023)
We investigate deep material networks (DMN). We lay the mathematical foundation of DMNs and present a novel DMN formulation, which is characterized by a reduced number of degrees of freedom. We present a efficient solution technique for nonlinear DMNs to accelerate complex two-scale simulations with minimal computational effort. A new interpolation technique is presented enabling the consideration of fluctuating microstructure characteristics in macroscopic simulations.